IMPLEMENTATION NOODWEEREXCESS IN PROVING EVIDENCE IN CASES OF ASSAULT (CASE STUDY OF THE DECISION AT THE MALILI DISTRICT COURT NO: 40/PID.B/2019/PN MLL) - Jodhi Kurniawan (Judge : Jurnal Hukum, 2025)
This study examines the application of the concept of noodweerexcess (excessive forced defense) in proving criminal cases of assault in Indonesia. The case study focuses on the Malili District Court Decision Number: 40/PID.B/2019/PN MLL. The background of this study is the importance of law enforcement based on justice, certainty, and legal benefits, as mandated by Pancasila as the philosophical basis of the Indonesian state. This article highlights the differences in views between the public prosecutor and the panel of judges regarding the application of Article 49 paragraph (2) of the Criminal Code regarding noodweerexcess in this case. The author analyzes the legal facts revealed in the trial and the judge's considerations , and provides a critical view of the judge's decision that stated the defendant could not be convicted for using excessive forced defense. This study concludes that the application of Article 49 of the Criminal Code in this case is considered inappropriate because one of the elements of the article is not supported by the facts of the act as stated in the case file. The author also provides suggestions regarding improving coordination between law enforcement officers and accuracy in the application of the article